Study of contact-impact force models in multibody mechanical systems - Flores, Paulo (2004)
This work deals with the contact-impact force models for spherical and cylindrical shaped surface collisions in multibody mechanical systems. The impact phenomenon is characterized by abrupt changes in the values of system variables, most commonly discontinuities in the system velocities. Other effects directly related to the impact phenomena are those of vibration propagation through the system, local elastic/plastic deformations at the contact zone and frictional energy dissipation. Impact is a prominent phenomenon in many mechanical systems such as mechanisms with intermittent motion and mechanisms with clearance joints [1,2]. Therefore, in order to correctly simulate and design these kinds of mechanical systems adequately, some appropriate contact-impact force model must be adopted.